2023
DOI: 10.15252/embj.2021110454
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for existence of an apoptosis‐inducing BH3‐only protein, sayonara, in Drosophila

Abstract: Cells need to sense stresses to initiate the execution of the dormant cell death program. Since the discovery of the first BH3‐only protein Bad, BH3‐only proteins have been recognized as indispensable stress sensors that induce apoptosis. BH3‐only proteins have so far not been identified in Drosophila despite their importance in other organisms. Here, we identify the first Drosophila BH3‐only protein and name it sayonara. Sayonara induces apoptosis in a BH3 motif‐dependent manner and interacts genetically and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Even complete starvation does not kill ISCs, which outlive the organism during starvation ( Fig S1A and B ). We recently found the first BH3-only protein, Sayonara (synr), in Drosophila ( Ikegawa et al, 2023 ). Synr activates caspases through the Bcl-2 pathway, relatively moderately compared with Rpr-induced DIAP1 inhibition ( Fig 1A ) ( Ikegawa et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even complete starvation does not kill ISCs, which outlive the organism during starvation ( Fig S1A and B ). We recently found the first BH3-only protein, Sayonara (synr), in Drosophila ( Ikegawa et al, 2023 ). Synr activates caspases through the Bcl-2 pathway, relatively moderately compared with Rpr-induced DIAP1 inhibition ( Fig 1A ) ( Ikegawa et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…We recently found the first BH3-only protein, Sayonara (synr), in Drosophila ( Ikegawa et al, 2023 ). Synr activates caspases through the Bcl-2 pathway, relatively moderately compared with Rpr-induced DIAP1 inhibition ( Fig 1A ) ( Ikegawa et al, 2023 ). We found that mild activation of caspases by Synr, while inducing cell death in the wing disc, causes massive expansion of esg >GFP-labelled progenitor cells rather than cell death in the R4 region, where tissue turnover readily occurs ( Ciesielski et al, 2022 ) ( Fig 1B–D ).…”
Section: Resultsmentioning
confidence: 99%
“…Since the BNIP3 specifically decreases rbf1 -induced apoptosis but does not modulate debcl -induced apoptosis, BNIP3 could act upstream of Debcl. Even without a BH3 sequence [9], the anti-apoptotic effect of BNIP3 suggests a possible interaction with Bcl2 family members. For example, an interaction of BNIP3 with Sayonara (the unique BH3-only Bcl-2 family member in Drosophila ) could block Sayonara’s binding to Buffy/Debcl.…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila , only three members of the Bcl-2 family have been identified. Two are mainly pro- apoptotic, Debcl [7,8] and Sayonara [9], and one is primarily anti-apoptotic, Buffy [10]. We have previously shown that over-expression of rbf1 , the Drosophila pRB homolog, induces mitochondrial apoptosis in epithelial tissues such as wing imaginal discs [11].…”
Section: Introductionmentioning
confidence: 99%
“…Finding such proteins by sequence homology is problematic, as the necessary homology is low (Banjara et al , 2020). In a recent publication, a Drosophila BH3‐only protein has been identified and characterized (Ikegawa et al , 2023). The authors show that the newly identified Sayonara (Synr) protein contains a domain that fits well with the consensus BH3 structure and is well‐conserved in Diptera.…”
Section: Figure Simplified Bcl‐2 Pathways In Worms Mammals and Flies;...mentioning
confidence: 99%